Neuorientierung der Raumordnungspolitik? Die neuen „Leitbilder und Handlungsstrategien für die Raumentwicklung in Deutschland” in der Diskussion - Blotevogel, Hans H. (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
The article discusses the “Concepts and Action Strategies for Spatial Development in Germany” adopted on 30th June 2006 by the Standing Conference of Ministers Responsible for Spatial Planning. It considers the context, the function and the central message of the document as well as in detail the three guiding visions (Leitbilder). The author analyses both the innovative content of the document and its conceptual consistency; he also explores the question of to what extent the new guiding visions signalise a paradigm shift in spatial planning policy to the detriment of the aim of balanced regional development in favour of growth, competitiveness and the market, and thus also an acceptance of greater regional disparities. The conclusion is that there is in fact no paradigm shift taking place in spatial planning policy, but equally that the new guiding visions are by no means a plea for everything simply to continue as before. Three new accents can be distinguished: firstly, a special emphasis on the aim of growth and innovation, secondly, a re-interpretation of the aim of securing the supply of basic and essential infrastructure, in particular against the background of demographic change, and thirdly, a more detailed specification of aims with regard to the safeguarding of natural resources and the shaping of cultural landscapes.